The Sorcerer as Apprentice: Trial, Error, and Chord Magic in Wagner's Overture to 'Die Feen'. Issue 1 (20th May 2019) - Vande Moortele, Steven
Abstract: Near the beginning of the overture to Wagner's first opera, Die Feen, appears a strikingly unusual harmonic progression: a string of five major triads related by ascending fifths that, as a non-functional sequence of back-relating applied dominants, has a centrifugal effect that quickly spins out of tonal control. After showing how this progression is connected to the magical subject matter of the opera, the article analyses both the progression itself and its role in the larger formal context of the overture in view of Wagner's musical training, his engagement with contemporary repertory models and, ultimately, his self-image as a Romantic composer. It is argued that Wagner's early chord magic comes into being through the manipulation of models with which he was familiar, and that the confrontation with these same models is the source both of his lifelong insecurity about his technical skills and of his urge to stylize himself as a musical magician.